Cryptic trans-lithospheric fault systems at the western margin of South America: implications for the formation and localization of gold-rich deposit superclusters - Wiemer, Daniel; Hagemann, Steffen G.; Hayward, Nicholas; Begg, Graham C.; Hronsky, Jon; Thébaud, Nicolas; Kemp, Anthony I. S.; Villanes, Carlos (Frontiers in Earth Science, 2023)
We present a review of frontier research advances in the investigation of cryptic structures that transect the South American Andes at oblique strike directions. The intersections between these cryptic structures and the superimposed Andean belt correlate with the spatial distribution of gold-rich mineral deposit clusters. The deposit clusters can be described as superclusters, as they comprise various gold deposit types that formed at multiple times throughout the Phanerozoic, impinging repeatedly on the structural intersections. However, the cryptic inherited fault structures are difficult to detect, because their deeper-seated roots are often overlain by younger supracrustal successions, and/or their exposed surface manifestations are structurally obscured by subsequent tectonic-magmatic activity. Thus, it also remains a challenge to constrain the nature and timing of formation, and the respective subsequent evolutionary path, of these proposed pre-Andean structures. Based on various case studies, we demonstrate that the localization of identified Phanerozoic gold deposit superclusters along the western South American margin is fundamentally controlled by structural inheritance often dating back to at least the Mesoproterozoic. Integration of multi-approach observations and datasets allows insights into a larger-scale tectonic history that showcases the successive inheritance of major structures originating from the Amazonian Craton, over the Paleozoic Gondwana margin, into the Cenozoic magmatic belts of the Andes, and even into recent fractures within the subducting oceanic Nazca plate, recording > 1.2-billion-years of progressive structural inheritance and growth at one of the longest-lived tectonic margins in Earth history. In contrast to previous models of the spatial distribution of gold deposits, based on statistical approaches and spatial periodicity in self-organized systems focusing on single subduction and/or accretion episodes and belts, we propose that the structural inheritance and intersections are key to the localization of gold deposits in the Andes. In combination with bulk-geochemical data from magmatic rocks, we suggest that inherited structures maintained a trans-lithospheric connectivity to pre-fertilized gold enriched upper mantle reservoirs, which were tapped during multiple tectono-magmatic reactivation episodes.